Green Chemical Processing and Synthesis 2017
DOI: 10.5772/intechopen.68388
|View full text |Cite
|
Sign up to set email alerts
|

Environment-Friendly Approach in the Synthesis of Metal/ Polymeric Nanocomposite Particles and Their Catalytic Activities on the Reduction of p-Nitrophenol to p-Aminophenol

Abstract: In this chapter, an environment-friendly approach in synthesizing Au and Au@Ag metal nanoparticles using a microgel is demonstrated. Poly(N-isopropyl acrylamide)/polyethyleneimine microgel was used as a multifunctional template to reduce metal ions to metal nanoparticles, stabilize and immobilize these metal nanoparticles, and regulate their accessibility within the template. Such multifunctional roles of microgel template were possible due to their unique properties (i.e., amino groups reducing capability, el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 83 publications
1
3
0
Order By: Relevance
“…The difference of the measured sizes is the chitosan layer that capped the silver nanoparticles. Dynamic light spectrophotometry has been noted to capture both the nanocomposite particle and the capping layer, as seen also in a previous study by Tan and Lee 56 on metal/polymeric nanocomposite particles. The particle size distribution of the optimum sample, shown in Figure 6 , exhibits a distribution curve skewed to the left.…”
Section: Resultssupporting
confidence: 71%
“…The difference of the measured sizes is the chitosan layer that capped the silver nanoparticles. Dynamic light spectrophotometry has been noted to capture both the nanocomposite particle and the capping layer, as seen also in a previous study by Tan and Lee 56 on metal/polymeric nanocomposite particles. The particle size distribution of the optimum sample, shown in Figure 6 , exhibits a distribution curve skewed to the left.…”
Section: Resultssupporting
confidence: 71%
“…The reduction of 4-nitrophenol by borohydride ions in aqueous solution is by far the most used model reaction for testing the catalytic activity of metallic nanoparticles. [63][64][65]121 Its mechanism can be inferred from the well-studied reduction of nitrobenzene in solution. As early as 1898 F.…”
Section: Reduction Of 4-nitrophenol By Borohydride Ionsmentioning
confidence: 99%
“…This interaction between electron-deficient reactants (nitroarenes) and electron-rich nanoparticles allows a greater number of reactant molecules to reach the nanoparticles' surface, resulting in a faster reduction reaction. 246 Li et al 82 reported the synthesis of bimetallic (Ag + Au) hybrid microgels. They loaded gold NPs with varying concentrations in Ag-based hybrid microgels and observed that the k app value for the catalytic reductive reaction of 4NiP in the presence of each hybrid system increased with increasing the amount of Au NPs.…”
Section: Applicationsmentioning
confidence: 99%